Cannabis and Its Secondary Metabolites: Their Use as Therapeutic Drugs, Toxicological Aspects, and Analytical Determination - Gonçalves, Joana (2019)
Although the medicinal properties of Cannabis species have been known for centuries, the interest on its main active secondary metabolites as therapeutic alternatives for several pathologies has grown in recent years. This potential use has been a revolution worldwide concerning public health, production, use and sale of cannabis, and has led inclusively to legislation changes in some countries. The scientific advances and concerns of the scientific community have allowed a better understanding of cannabis derivatives as pharmacological options in several conditions, such as appetite stimulation, pain treatment, skin pathologies, anticonvulsant therapy, neurodegenerative diseases, and infectious diseases. However, there is some controversy regarding the legal and ethical implications of their use and routes of administration, also concerning the adverse health consequences and deaths attributed to marijuana consumption, and these represent some of the complexities associated with the use of these compounds as therapeutic drugs. This review comprehends the main secondary metabolites of Cannabis, approaching their therapeutic potential and applications, as well as their potential risks, in order to differentiate the consumption as recreational drugs. There will be also a focus on the analytical methodologies for their analysis, in order to aid health professionals and toxicologists in cases where these compounds are present.